The microglial innate immune receptor TREM2 participates in fear memory formation through excessive prelimbic cortical synaptic pruning - Zhang, Le-le; Cheng, Peng; Chu, Yuan-qing; Zhou, Zi-ming; Hua, Rong; Zhang, Yong-mei (Frontiers in Immunology, 2024)
Fear memory formation has been implicated in fear-and stress-related psychiatric disorders, including post-traumatic stress disorder (PTSD) and phobias. Synapse deficiency and microglial activation are common among patients with PTSD, and induced in animal models of fear conditioning. Increasing studies now focus on explaining the specific mechanisms between microglia and synapse deficiency. Though newly-identified microglia regulator triggering receptor expressed on myeloid cells 2 (TREM2) plays a role in microglial phagocytic activity, its role in fear-formation remains unknown. The results herein indicate that the foot-shock protocol in male mice resulted in a fear formation model. Mechanistically, fear conditioning enhanced the microglial capacity for engulfing synapse materials, and led to glutamatergic neuron activation in the prelimbic cortex. Prelimbic chemical deletion or microglia inhibition improved fear memory formation. Further investigation demonstrated that TREM2 regulates microglial phagocytosis, enhancing synaptic pruning. Trem2 knockout mice showed remarkable reductions in prelimbic synaptic pruning and reduced neuron activation, with decreased fear memory formation. Our cumulative results suggest that prelimbic TREM2-mediated excessive microglial synaptic pruning is involved in the fear memory formation process, leading to development of abnormal stress-related behavior.